ERBB2b mRNA isoform encodes a nuclear variant of the ERBB2 oncogene in breast cancer. Issue 12 (6th July 2020) - Hua, Guoqiang; Bergon, Aurélie; Cauchy, Pierre; Kahn‐Perlès, Brigitte; Bertucci, François; Birnbaum, Daniel; Benkirane‐Jessel, Nadia; Imbert, Jean
Abstract: The presence of nuclear ERBB2 receptor‐type tyrosine kinase is one of the causes of the resistance to membrane ERBB2‐targeted therapy in breast cancers. It has been previously reported that this nuclear location arises through at least two different mechanisms: proteolytic shedding of the extracellular domain of the full‐length receptor and translation of the messenger RNA (mRNA)‐encoding ERBB2 from internal initiation codons. Here, we report a new mechanism and function where a significant portion of nuclear ERBB2 results from the translation of the variant ERBB2 mRNA under the transcriptional control of a distal promoter that is actively used in breast cancer cells. We show that both membrane ERBB2a and nuclear ERBB2b isoforms are prevalently expressed in breast cancer cell lines and carcinoma samples. The ERBB2b isoform, which is translated from mRNA variant 2, can directly translocate into the nucleus due to the lack of the signal peptide which is required for an intermediate membrane location. Small interfering RNA‐mediated gene silencing showed that ERBB2b can repress ERBB2a expression, encoded by variant 1, whereas ERBB2a activates ERBB2b. Nuclear ERBB2 binding to its own promoter was revealed by chromatin immunoprecipitation assay. Altogether, our results provide new insights into the origin and function of nuclear ERBB2 where it can participate at the same time in a positive or a negative feedback autoregulatory loop, dependent on which of its promoters this bona fide transcription factor is acting. They also provide a new understanding for the resistance to therapies targeting the membrane‐anchored ERBB2 in breast cancer. Abstract : We demonstrate that the nuclear location of ERBB2 can results from the translation of a variant ERBB2 messenger RNA under the transcriptional control of a distal promoter, actively used in breast cancer cells. This ERBB2b isoform can directly translocate into the nucleus due to the lack of the signal peptide required for an intermediate membrane location. Our results provide new insights into the origin and function of nuclear ERBB2 where it can participate at the same time in a positive or a negative feedback autoregulatory loop, dependent on which of its promoters this bona fide transcription factor is acting.